Increased Oxidation as an Additional Mechanism Underlying Reduced Clot Permeability and Impaired Fibrinolysis in Type 2 Diabetes - Anna Lados-Krupa; Malgorzata Konieczynska; Artur Chmiel; Anetta Undas (Journal of Diabetes Research)
Aims. We sought to investigate whether enhanced oxidation contributes to unfavorable fibrin clot properties in patients with diabetes. Methods. We assessed plasma fibrin clot permeation (Ks, a measure of the pore size in fibrin networks) and clot lysis time induced by recombinant tissue plasminogen activator (CLT) in 163 consecutive type 2 diabetic patients (92 men and 71 women) aged 65 ± 8.8 years with a mean glycated hemoglobin (HbA1c) of 6.8%. We also measured oxidative stress markers, including nitrotyrosine, the soluble form of receptor for advanced glycation end products (sRAGE), 8-iso-prostaglandin F2α (8-iso-PGF2α), oxidized low-density lipoprotein (oxLDL), and advanced glycation end products (AGE). Results. There were inverse correlations between Ks and nitrotyrosine, sRAGE, 8-iso-PGF2α, and oxLDL. CLT showed a positive correlation with oxLDL and nitrotyrosine but not with other oxidation markers. All these associations remained significant for Ks after adjustment for fibrinogen, disease duration, and HbA1c (all P<0.05), while oxLDL was the only independent predictor of CLT. Conclusions. Our study shows that enhanced oxidative stress adversely affects plasma fibrin clot properties in type 2 diabetic patients, regardless of disease duration and glycemia control.